If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5u + -13 = -2(u + -7) Reorder the terms: -13 + -5u = -2(u + -7) Reorder the terms: -13 + -5u = -2(-7 + u) -13 + -5u = (-7 * -2 + u * -2) -13 + -5u = (14 + -2u) Solving -13 + -5u = 14 + -2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2u' to each side of the equation. -13 + -5u + 2u = 14 + -2u + 2u Combine like terms: -5u + 2u = -3u -13 + -3u = 14 + -2u + 2u Combine like terms: -2u + 2u = 0 -13 + -3u = 14 + 0 -13 + -3u = 14 Add '13' to each side of the equation. -13 + 13 + -3u = 14 + 13 Combine like terms: -13 + 13 = 0 0 + -3u = 14 + 13 -3u = 14 + 13 Combine like terms: 14 + 13 = 27 -3u = 27 Divide each side by '-3'. u = -9 Simplifying u = -9
| 4x^3-8=100 | | 3.2+x=7.45 | | 9(y-4)=3y-6 | | x^3-3x=21 | | (3x^3+10x+5)-(x^3+4x-6)= | | -2x-23=3(x+4) | | 4c^3-8=100 | | -6(U+2)=4u+38 | | -3v+5(v-2)=-20 | | 14=5(x+5)+6x | | 14=4(w-4)-7w | | -c(5)-23=-18 | | x+16=2x+4 | | x+16=2x+3 | | 48+3w+10w=100 | | (8x^2)+(3x^2-2)= | | -3q^2+30q-48=0 | | 3x-90=46 | | 2x+6=2(x-8)+10 | | 4x^2-9y^2-16x-18y=29 | | m+(-13)=(-18) | | 293=3x | | 4/5/17+y=6/16/17 | | x=-3y+17 | | 4y^2+16y+21= | | y=3.5x+6.1 | | -6(3x-6)=120 | | -23=2x+3(-x-4) | | -2=-15-x | | 6z+24=6z+4 | | 6y-4-3y+1= | | 4(2m+1)=36 |